jonnburton
Junior Member
- Joined
- Dec 16, 2012
- Messages
- 155
I have been working through this worked example (on finding the eigenvalues) for a matrix and can't understand a step in the working.
Expanding the determinant ends up in:
\(\displaystyle (1-\lambda)\{\lambda^2-\lambda - 3\}+1-\lambda = 0\)
\(\displaystyle 1 -\lambda = 0 \) or \(\displaystyle \lambda^2 -\lambda -2 = 0\)
But, surely the last statement should be \(\displaystyle \lambda^2 -2\lambda -2 = 0\)
If not, what has happened to the \(\displaystyle - \lambda\) at the end?
Any information would be much appreciated!
Expanding the determinant ends up in:
\(\displaystyle (1-\lambda)\{\lambda^2-\lambda - 3\}+1-\lambda = 0\)
\(\displaystyle 1 -\lambda = 0 \) or \(\displaystyle \lambda^2 -\lambda -2 = 0\)
But, surely the last statement should be \(\displaystyle \lambda^2 -2\lambda -2 = 0\)
If not, what has happened to the \(\displaystyle - \lambda\) at the end?
Any information would be much appreciated!